(untitled) (GEOgraphia, 2009)
Resumo: A Geografia Histórica é uma parte da Geografia que sempre esteve presente na história e interpretações dos espaços desta ciência. Às vezes colocada no esquecimento, às vezes voltando a ocupar um lugar de grande importância, a Geografia Histórica cumpre um papel fundamental no desenvolvimento da teoria e do método, sobretudo no atual momento. Abstract: Historical Gcography is a part of Geography that has always been present in history and interpretations about spaces on this science. Has sometimes been forgotten and returns other times to occupy a great important place. Historical Geography has a fundamental papa about development of theory and rnethod, specially at current moment.